2021
DOI: 10.3390/plants10030452
|View full text |Cite
|
Sign up to set email alerts
|

The Diverse Salt-Stress Response of Arabidopsis ctr1-1 and ein2-1 Ethylene Signaling Mutants Is Linked to Altered Root Auxin Homeostasis

Abstract: We explored the interplay between ethylene signals and the auxin pool in roots exposed to high salinity using Arabidopsisthaliana wild-type plants (Col-0), and the ethylene-signaling mutants ctr1-1 (constitutive) and ein2-1 (insensitive). The negative effect of salt stress was less pronounced in ctr1-1 individuals, which was concomitant with augmented auxin signaling both in the ctr1-1 controls and after 100 mM NaCl treatment. The R2D2 auxin sensorallowed mapping this active auxin increase to the root epiderma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 71 publications
0
3
0
Order By: Relevance
“…Physiological, biochemical and genetic studies have provided ample evidence in support of the key role of auxin in triggering abiotic stress-mediated differential modifications in the root system architecture of plants [ 21 ]. The key role of the maintenance of auxin homeostasis in regulating salinity stress tolerance is emerging in plant biology [ 22 ]. In the present study, in order to better understand the mechanisms conferring rice adaptation to salinity stress, we conducted a comparative analysis of various auxin-related genes (which regulate auxin homeostasis) in the roots of salt sensitive IR64 and salt tolerant Luna Suvarna (LS) cultivars of rice under optimal as well as salinity stress conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Physiological, biochemical and genetic studies have provided ample evidence in support of the key role of auxin in triggering abiotic stress-mediated differential modifications in the root system architecture of plants [ 21 ]. The key role of the maintenance of auxin homeostasis in regulating salinity stress tolerance is emerging in plant biology [ 22 ]. In the present study, in order to better understand the mechanisms conferring rice adaptation to salinity stress, we conducted a comparative analysis of various auxin-related genes (which regulate auxin homeostasis) in the roots of salt sensitive IR64 and salt tolerant Luna Suvarna (LS) cultivars of rice under optimal as well as salinity stress conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Members of the RAF family, such as RAF5 and RAF8, possibly expressed in diverse tissues with increased expression in A. thaliana , demonstrating broad response patterns against salt stress [ 33 ]. The results revealed that the ability of the CTR1-1 mutant of the RAF-like kinase to resist high salinity is connected to an altered ethylene/auxin regulatory loop in Arabidopsis [ 70 ]. Salt stress in cotton causes a disturbance in the dynamic ion balance in plants, changes the average permeability of the membrane, reduces the activity of several membrane-bounded enzymes, and results in a variety of metabolic problems [ 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that the increased rate of ethylene production, as a consequence of salt stress, actually causes some of the symptoms of stress or induces acclimation processes [132]. Moreover, ethylene-mediated molecular mechanisms are implicated in the acclimation response to salt stress through the regulation of free proline accumulation and increased ROS scavenging in Arabidopsis [133]. The application of ethylene or its precursor ACC improves plant tolerance to high salinity, largely by increasing the expression of ROS scavengers [62,134].…”
Section: Regulation Of Ethylene Signaling For Environmental Stress Ac...mentioning
confidence: 96%